2017
DOI: 10.1371/journal.pone.0189323
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations in antagonist co-activation: Role in the repeated-bout effect

Abstract: Eccentric exercise results in an adaptation which attenuates muscle damage from subsequent exercise—termed the “repeated-bout effect (RBE).” Purpose: Study examined antagonist co-activation and motor-unit recruitment strategy, assessed via dEMG, concomitant to the RBE. Methods: Nine participants performed 5 sub-maximal isometric trapezoid (ramp-up, hold, ramp-down) contractions at force levels corresponding to 50% and 80% of maximal isometric strength (MVC). Surface EMG signals of the biceps brachii were decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…This greater efficiency could translate into a lesser cardiometabolic demand and perceived exertion during Ex2. Changes in motor recruitment pattern could be explained by different mechanisms such as (I) a shift in motor unit recruitment toward low-threshold motor units during the second bout (6); (II) an enhanced synchronization of motor units (6); (III) a lower antagonist muscle activation (36), although no significant difference in BF EMG activity during the stance phase in the present study; and (IV) an attenuation of supraspinal fatigue (18). Moreover, Hyldahl et al (6) reported that muscle stiffness might increase by skeletal muscle extracellular matrix remodeling after eccentric exercise, which may protect muscle from damage during a subsequent eccentric exercise.…”
Section: Discussionmentioning
confidence: 99%
“…This greater efficiency could translate into a lesser cardiometabolic demand and perceived exertion during Ex2. Changes in motor recruitment pattern could be explained by different mechanisms such as (I) a shift in motor unit recruitment toward low-threshold motor units during the second bout (6); (II) an enhanced synchronization of motor units (6); (III) a lower antagonist muscle activation (36), although no significant difference in BF EMG activity during the stance phase in the present study; and (IV) an attenuation of supraspinal fatigue (18). Moreover, Hyldahl et al (6) reported that muscle stiffness might increase by skeletal muscle extracellular matrix remodeling after eccentric exercise, which may protect muscle from damage during a subsequent eccentric exercise.…”
Section: Discussionmentioning
confidence: 99%
“…These responses may be incongruent with the longer-term supressed responses of the antagonist muscle which may be expected with the downregulation of antagonist activity accompanying improvements in muscular strength. There is early evidence to suggest that shifts in co-activation during training are observable following just a single session of training (Hight et al 2017); however, this is yet to be thoroughly examined.…”
Section: A Bout Of Heavy-loaded Strength Training Has Differential Efmentioning
confidence: 99%